Indigenous Economies for Post-Covid Development: Lessons from the North Rupununi, Guyana - Mistry, Jayalaxshmi; Jafferally, Deirdre; Albert, Grace; Xavier, Rebecca; Robertson, Bernie; George, Ena; Mendonca, Sean; Berardi, Andrea (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
Despite being disproportionately susceptible to infectious diseases like COVID-19, many Indigenous peoples still hold traditional knowledge that is responding and adapting to new circumstances and crises such as the pandemic. In this paper, we present the findings from a participatory video project in eight Makushi and Wapishan Indigenous communities in the North Rupununi, Guyana, that explored the difficulties and disruptions that came about through COVID-19, but also the opportunities for change and transformation. Over four months, Indigenous researchers gathered the views and perspectives of their communities through a participatory video process. Our findings show that there was limited information provided to communities and their leaders (especially at the start of the pandemic), and support, in the form of supplies and relief, was ad-hoc and inconsistent. As people lost income from paid work, they turned to traditional farming, fishing and hunting to sustain their lives and to support others who did not have the conditions to support themselves. While many Indigenous community members retreated to their isolated farms as a protective measure, community leaders took responsibility to protect their lands and territory by installing gates on access roads and establishing patrols to enforce rules. The recognition that their traditional knowledge was not only culturally important but necessary for survival during the pandemic, gave it a newfound relevance and legitimacy, particularly for young people. Supporting Indigenous economies such as farming are not only critical for maintaining nature and traditional cultures today, but also for being resilient to future social and ecological crises.